Ecological environmental flow estimation for rivers with complicated hydraulic conditions - Xiaolong Liu; Hanlin Song; Yufeng Ren; Meixiu Yu; Yixuan Liu; Dewei Wang; Fei Xia; Chunsheng Tang; Li Tian; Wuxin Dong; Jiayi He; Ting Fu (Water Science and Technology, 2024)
Estimating ecological environmental flow in tidal rivers is one of the major challenges for sustainable water resource management in estuaries and river basins. This paper presents an ecological environmental flow framework that was developed to accommodate highly dynamic medium tidal estuaries found along the Yellow Sea coast of China. The framework not only proposes a method of water quality-based ecological flow for tidal gate-controlled rivers but also proposes a method of water demand for scouring and silting to protect ports in coastal viscous sediment environments. The framework integrates the instream water requirements of water quality, sediment and basic ecological flow, and considers the temporal and spatial variation differences for the environmental flow requirements of tidal rivers. This study emphasizes the significance and necessity of continuous monitoring of ecological data in determining the environmental flow of tidal rivers. The output of this study could provide vital references for decision-making and management of the water resource allocation and ecological protection in tidal rivers. HIGHLIGHTS This study develops an ecological environmental flow framework for highly dynamic medium tidal estuaries.; This study suggests a method of water quality-based ecological flow for tidal gate-controlled rivers.; This study proposes a method of water demand for scouring and silting.;